Analysis of Civil Engineering Students' Mathematical Thinking Skills in Calculus Based on Personality Type - Intan Sari; Defry Basrin; Fazrina Saumi; Mawarni; Fairuz; Fitra Muliani (Mandalika Mathematics and Educations Journal, 2026)
Mathematical thinking skills are crucial competencies for civil engineering students in dealing with increasingly complex infrastructure problems, one of the foundations of which is laid by basic calculus. However, students show varying abilities, indicating the influence of internal factors such as personality. This study aims to describe the relationship between students' personality types, as measured by the Myers–Briggs Type Indicator (MBTI) framework, and the mathematical thinking abilities of civil engineering students in calculus learning. This study uses a descriptive qualitative approach involving civil engineering students at Samudra University. Personality types were determined using the MBTI questionnaire, while mathematical thinking skills were measured by analyzing students' written answers to calculus problems compiled based on mathematical thinking indicators. Data were analyzed descriptively and qualitatively to identify patterns in mathematical thinking skills across personality types. The results of the study indicate that students with ESFJ or SFJ tendencies tend to show strength in applying concrete procedures (specializing), while students with ENFJ or NFJ tendencies tend to demonstrate greater flexibility in developing intuitive ideas. This study suggests that students' personalities should be taken into account when designing calculus learning. The application of adaptive and differentiated learning strategies tailored to individual personality characteristics may be considered.